RO Membrane to Remove Sulfate: an Inland Brackish Water Desalination Pilot Study - Chang, Qigang; Bergantine, Brian R.; Johnson, Robert Bo; Veerapaneni, Srinivas Vasu; Hall, Troy B.; Peterson, Mark A.; Buchholz, David (Journal of Membrane and Separation Technology, 2014)
The City of Fargo completed a Facility Plan of their Water Treatment Plant (WTP) in 2011 to address two main issues: increasing water demands and high sulfate concentrations within a raw water source (Sheyenne River) primarily due to Devils Lake flooding. Reverse Osmosis (RO) was recognized as the most appropriate technology for sulfate reduction, and recommended for use in the WTP expansion. An RO pilot study was performed to evaluate its feasibility for two operational scenarios. RO membranes experienced rapid fouling in the Polishing Scenario, which used RO to further treat filtered water from the existing WTP (pretreatment, lime softening, ozone, and granular filtration). RO membranes exhibited superior performance in the Parallel Scenario, which was a separate treatment process (coagulation/flocculation/sedimentation + microfiltration/ultrafiltration +RO) parallel to the existing WTP. RO membrane autopsies indicated that membrane fouling was organic and biological for the Polishing Scenario while organic and scaling for the Parallel Scenario. Optimization studies were performed in the Parallel Scenario to determine optimal coagulation conditions for pretreatment as well as flux, recovery, and membrane cleaning regimes for both the MF/UF and the RO. Uniquely, an RO membrane selection pilot was conducted for both scenarios to evaluate RO membranes from four different manufacturers. The slight difference surface chemistry among various RO membrane can cause substantial different performance. It was found that one RO membrane could not be cleaned adequately, although it has many successful applications elsewhere. This one year pilot study proved that RO technology is feasible to reduce sulfate concentrations to acceptable levels in the City’s finished water.